THE ESSENCE AND EVOLUTION OF STRATEGIC BUSINESS MANAGEMENT - ZAKHARCHUK, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the theoretical foundations of strategic enterprise management, the evolution of strategic management, the essence, critical approaches, and principles of strategic enterprise management. It is noted that the term «strategy» was first used by A. Chandler in 1962 and the term «strategic management» by I. Ansoff in 1965. The evolution of strategic planning was studied. I. Ansoff identified four stages of strategic management development, in particular: Stage I – reactive (Chandlerian) adaptation, Stage II – strategic planning, Stage III – management of strategic opportunities, and Stage IV – management of problems on a real-time scale. Namely: Stage I – budgeting and control, Stage II – long-term planning, Stage III – strategic planning, and Stage IV – strategic market management. The strategies of the school were analyzed, which were analyzed in detail in the work of H. Mintzberg, B. Ahlstrand, and J. Lempel. These schools can be grouped according to the nature of research into three groups in the following group: Group I – includes three schools: design, planning, and positioning; II group – consists of six schools: entrepreneurial, cognitive (cognitive), school of education, power (force), culture and external environment; III group – includes one school: configurations. The article analyzes the existing definitions of the essence of the concept of «strategic management», which means the processes of making managerial decisions or sets of decisions; management process; action model; management of the organization based on human potential, etc. The author’s definition of strategic management has been formulated, which should be understood as the specific processes of making and implementing management decisions regarding the formation and implementation of a strategy with the targeted achievement of established goals, which are based on an objective assessment of the external and internal conditions of the enterprise’s functioning.